New Model of Educational Administration with Non-Classroom in Pandemic Era - Siririn, Jakkrit (National Interest, 2021)
COVID-19 (Coronavirus 2019 or SARS CoV-2) that are currently spreading. It has a direct impact on the management of educational institutions around the world. Many institutions are trying to rush to find a way out and there are guidelines for solving problems with many measures, such as online teaching and learning management or e-Learning or opening online registration. In particular, Blended Learning is applied to the teaching and learning management in the transitional age from Lecture-based Learning to Online-based Learning in Thailand and a combination of teachers of the two generations. Through the integration of classroom teaching and education with online education. The key is the search for Non-classroom performance tools and ideas that will help enhance learners' learning and balancing classroom time appropriately in the COVID-19 era, whether it is Hybrid Home School or Temporary Home School.